2023
DOI: 10.23887/ijerr.v6i1.59582
|View full text |Cite
|
Sign up to set email alerts
|

Life Skills of Filipino Emerging Adults of a Catholic Higher Education Institution in Central Philippines

Abstract: Life skills are essential among students in countering the circumstances of life. However, due to the shifting instructional modality, their skills acquisition was compromised. Thus, this study aims to analyze the life skills of Filipino emerging adults in terms of self-awareness, empathy, effective communication, interpersonal relations, creative thinking, critical thinking, decision-making, problem-solving, coping with emotions, and coping with stress. Likewise, it determined the relationship between the dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Most students during this circumstance were not prepared for this abrupt implementation of this instructional set-up (Alic & Bual, 2021). These students tried to participate but they were at the mercy of their available gadgets and connectivity (Pahilanga et al, 2023;Rios et al, 2023). They were also given modules to accomplish but were used to actual instructions by their teachers which compromised their interest and focus to engage in the process (Cena & Bual, 2021;Kim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Most students during this circumstance were not prepared for this abrupt implementation of this instructional set-up (Alic & Bual, 2021). These students tried to participate but they were at the mercy of their available gadgets and connectivity (Pahilanga et al, 2023;Rios et al, 2023). They were also given modules to accomplish but were used to actual instructions by their teachers which compromised their interest and focus to engage in the process (Cena & Bual, 2021;Kim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Baraily et al (2021), Ecang and Petalla (2022), and Pahilanga et al (2023) found that most of the instructions during the pandemic failed to connect the lessons to the students' lives, making the instructions superficial. Also, Miguel-Revilla (2022) found that most students did not see the relevance of World History since the discussions talked about the past, which has nothing to do with the present.…”
Section: Students' Thinking Skills In World Historymentioning
confidence: 99%
“…It is an educational approach that combines content and skills. Without these skills, educators may resort to traditional methods such as rote memorization and passive classroom instructions [49,50,51,52,53].…”
Section: Extent Practice Of 21 St Century Teaching Skills Of Teachersmentioning
confidence: 99%